“You have to do it with love… Oral history was something I was never paid for…”: An Interview with Professor Alessandro Portelli (Sapienza Università di Roma) - Wohlmuth, Petr (Dějiny – teorie – kritika, 2022)
... said Alessandro Portelli (*1942), an eminent oral historian and scholar who gave us an interview in late May on the premises of Circolo Gianni Bosio archives in Rome. This important institution has been involved in the field of oral history and ethnomusicology in Italy for many decades. The status of oral history in Italy considerably differs compared to other European countries; on the one hand, it still must fight its way through academic institutions, on the other hand, however, it represents a remarkably strong and vibrant community. In addition to being largely responsible for initiating the cultural turn in the discipline during the 1980s, this community engages in large-scale research projects and has long been providing the global oral history field with some of the most significant texts. Petr Wohlmuth spoke with Alessandro Portelli in Rome in May 2022.